2014
DOI: 10.1007/s00192-013-2263-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Pelvic Floor Distress Inventory (PFDI-20) and Pelvic Floor Impact Questionnaire (PFIQ-7) in a Dutch population

Abstract: For assessing distress and health-related quality of life of pelvic floor dysfunction, the Dutch PFDI-20 and PFIQ-7 are reliable and valid in the general Dutch population, and also responsive and interpretable among tertiary care-seeking women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 24 publications
11
64
3
Order By: Relevance
“…Our results show psychometric validity for PFDI-20 questionnaire and are comparable with previous validation studies [810]. In our study, PFIQ-7 had some limitations whereas Teleman et al found acceptable psychometric properties in the Swedish version of PFIQ-7 [9].…”
Section: Discussionsupporting
confidence: 90%
“…Our results show psychometric validity for PFDI-20 questionnaire and are comparable with previous validation studies [810]. In our study, PFIQ-7 had some limitations whereas Teleman et al found acceptable psychometric properties in the Swedish version of PFIQ-7 [9].…”
Section: Discussionsupporting
confidence: 90%
“…Age (years, X(SD)) 53.7(9.7) Parity (Md(IQR)) 2(1) Body mass index (X(SD)) 27 Dutch have studied the responsiveness of PFDI-20 and PFIQ-7 [2,9,11,13,14]. In the present study many similar results were found when compared to the other responsiveness studies.…”
Section: Tablesupporting
confidence: 92%
“…Regarding these findings, the experience shows that women often indicate that the urinary symptoms have more impact than POP symptoms, which is consistent with the results found in the present study. Furthermore, in both questionnaires, the subscales that demonstrated less responsiveness were the colorectal-anal subscales; in the other validation studies the urinary and POP subscales also demonstrated more responsiveness than the colo-rectal scales [2,9,11,13,14]. This may be because in the sample of this study the smallest clinic percentage was for women with colorectal-anal symptoms, and a specific clinic has the largest changes in the subscales that assess this clinic was accepted (for example, the UI have more changes in UDI and UIQ) [30].…”
Section: Tablementioning
confidence: 94%
See 2 more Smart Citations